Mo-Dopant-Enhanced Energy Storage Performance of VS2 Microflowers as Electrode Materials for Supercapacitors - Jingwei Wang; Xuejun Zheng; Long Xie; Zhenhua Xiang; Wenyuan He (Inorganics, 2025)
It is found that Mo doping can enhance the supercapacitor performance of VS2 microflowers. The X-ray diffraction combined with energy dispersive X-ray, X-ray photoelectron spectroscopy, and Raman spectra results verify the successful doping of Mo atoms into the VS2 matrix. As the electrode material of supercapacitors, the Mo-doped VS2 performs better electrochemical performance than pristine VS2, achieving the specific capacitance of 170 F g−1 at 0.5 A g−1 and 389.5 F g−1 at 5 mV s−1. Furthermore, the symmetric supercapacitor based on the Mo-doped VS2 exhibits good stability and ideal rate capability. The enhanced capability is presumably ascribed to the more accessible active sites and faster electrons/ions diffusion kinetics, which are caused by the increased specific surface area, expanded interlayer spacing, and improved conductivity after Mo doping. This strategy can also be extended to strengthen the capacitive properties of other transition metal dichalcogenides for advanced energy storage devices.